Facilitators and Barriers of HPV Vaccine Acceptance, Initiation, and Completion among LGBTQ Community in the U.S.: A Systematic Review. Issue 2 (3rd April 2022) - Hao, Zhichao; Guo, Yuqi; Bowling, Jessamyn; Ledenyi, Madeleine
Abstract: Objective: This study aims to identify facilitators and barriers of Human Papillomavirus (HPV) vaccine acceptance, initiation, and completion among LGBTQ (lesbian, gay, bisexual, trans, and queer) individuals. Method: A systematic review of qualitative and quantitative studies on HPV vaccine acceptance, initiation, and completion from 2006 to June 15, 2020 was performed in each database. Results: Twenty-six studies focusing on HPV vaccination among LGBTQ individuals were reviewed. Conclusions: Knowledge of HPV vaccine and healthcare providers' recommendations were identified as facilitators to receive HPV vaccinate, while high co-pay cost and concerns of the effectiveness and safety were identified as barriers.